Identifying key habitat and seasonal patterns of a critically endangered population of killer whales. (September 2014) - Esteban, Ruth; Verborgh, Philippe; Gauffier, Pauline; Giménez, Joan; Afán, Isabel; Cañadas, Ana; García, Pedro; Murcia, Jose Luis; Magalhães, Sara; Andreu, Ezequiel; de Stephanis, Renaud
<x content-type="archive" xml:space="preserve">Abstract</x> Killer whales have been described in the Gulf of Cadiz, southern Spain, in spring and in the Strait of Gibraltar in summer. A total of 11, 276 cetaceans sightings coming from different sources (dedicated research surveys, whale watching companies and opportunistic observations) were used to create two presence–'pseudo-absence' predictive generalized additive models (GAM), where presence data were defined as sightings of killer whales and 'pseudo-absence' data as sightings of other cetacean species. One model was created using spring data when killer whales' main prey, Atlantic bluefin tuna, enter the Mediterranean Sea, and the other model used summer data when Atlantic bluefin tuna return to the Atlantic Ocean. Both model predictions show that killer whales are highly associated with a probable distribution of bluefin tuna during their migration throughout the study area, constraining their distribution to the Gulf of Cadiz in spring and the Strait of Gibraltar in spring and summer. Knowledge of the distribution of killer whales in the study area is essential to establish conservation measures for this population.